Global Mexican Cultural Productions - Blanco-Cano, R. author. aut Link
XV, 259 p.
Keywords: In this book, the authors propose a multilayered reading of contemporary transnational cultural manifestations in which it is possible to recognize challenges and cultural strategies that transnational Mexican communities conceive in order to claim cultural, political and social agency.